Changements technologiques et rapports collectifs du travail - Côté, André (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
This paper focusses on the relationship between technological change and the labour relations system circumscribed by the Québec Labour Code. While a teleological interpretation of bargaining rights of certified associations by labour jurisdictions seems to have dealt adequately with the impact of such changes on certification, the doctrine of residual management rights, in the context of fixed-term agreements entrenched in the Québec Labour Code, appears to be, in the opinion of the author, unduly rigid and restrictive. The Freedman Report on Railway run-through and the subsequent discussions surrounding the Woods Commission Report in the 1960's, resulted in the inclusion in the Canada Labour Code of provisions pertaining to the possible adjustment, through collective bargaining, of collective agreements in the context of such technological changes. Various provisions to the same effect have subsequently been inserted in the Labour Codes of Saskatchewan, Manitoba and British-Columbia. The Report of the Beaudry Commission recently proposed that the Québec Labour Code be similary modified by the inclusion of analoguous provisions. The author suggests that a reform along the lines thus suggested is, in principle, desirable to ensure a more equitable adaptability of our legal categories to the imperatives of technological change.